Polymer nanocomposite membranes for bacteria removal - Taki Sultana, Chowdhury Suhi; Md. Ashraful, Hasan; Abrar, Ahmed; Faisal Islam, Chowdhury; Md. Rezaur, Rahman; Muhammad Khusairy, Bakri (Woodhead Publishing is an imprint of Elsevier, 2025)
Water contamination has been identified as a major environmental problem. Therefore developing new technology is essential to addressing this issue from an environmental perspective. To improve the technologies, membranes composed of nanocomposite materials are widely employed. Recently, there has been a lot of interest in the capacity of common polymeric membranes to separate many types of pollutants from water, including chemicals, bacteria, and colors. The primary objective of this chapter is to provide the latest advancements in the application of nanocomposite membranes for water treatment. A thorough explanation of the harm these contaminants bring to the ecosystem is included with a list of the principal contaminants found in water sources. The usage of nanocomposite membranes in desalination, dye removal, nanoparticle separation, antibacterial applications, separation of inorganic contaminants, and removal of naturally occurring organic components is shown and discussed in this chapter. This chapter also aims to provide a better understanding of the primary pollutants present in water sources as well as the various membrane separation techniques. The world’s population will have more access to sustainable and clean water if these pollutants are eliminated.